Features Of Adolescent And Teacher Cooperation In The Current Period In Choosing A Profession - Zukhra Mirzotilloyevna Radjabova (Academia One Publishing, 2023)
This article analyzes the communicative position of adolescents by classes in accordance with the communicative activity of the teacher,identifies the communicative zone of the group in the collaboration of adolescents with the teacher in the choice of profession.The communicative nature of the teacher in the activities of cooperation with adolescents in many ways occupies a special place in managing the educational process, determining its results and mastering the knowledge of the learner, determining his attitude to the subject of study and forming as a person
Keywords: Adolescent; Communicative; Respondent